La decena - Rodríguez Luján, Milagros Caridad (2019)
The session called "The Ten", was developed in the area of mathematics keeping in mind the approach of solving quantity problems from the necessary resources such as capabilities, translates amounts to numerical expressions, communicates its understanding of numbers and operations, uses estimation and calculation strategies and procedures, argues claims about numerical relationships and operations; related to each other has been able to achieve in students the performance that establishes relationships between data and one or more actions such as add, remove, advance, rollback, join, separate, compare and match amounts, and transforms them into expressions (model) addition or subtraction with natural numbers up to two digits. _x000D_ _x000D_ The present session was based on the dialogue and communication of the purpose of the session "Today they will express numbers until the ten with various representations", where it is explained to the students who observe carefully during the course of the session, the groupings that they form with the specific material to determine a quantity and represent it with numbers.